Lean management in quality improvement of cutting and hot forming process for window tint - Azizol Heirey, Bahari; Zamzuri, Hamedon (Universiti Malaysia Pahang, 2022)
The objective of this study is to describe the application of the DMAIC (Define, Measure, Analyze, Improve, and Control) technique at a Malaysian company that forms and cuts window tint film. This case research focuses on the Define, Measure, Analyze, Improve, and Control (DMAIC) phases for a full and effective project implementation and presentation. According to the findings of this case study, dust is a significant flaw in the cutting process. It was also discovered that the upgrades initiative directly benefits others, including economic benefits. The application of this powerful tool has not only reduced the rate of defects, but also in the areas of product development, customer retention analysis, cycle time optimization, productivity improvement and market share.